2013
DOI: 10.1016/j.ijsu.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of liver regeneration in rats: Description of an animal model for liver regeneration studies

Abstract: Seventy percent partial hepatectomy in healthy rats induces a rapid regenerative response and PODs 2, 4 and 8 seems optimal for assessing hepatic growth in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…In total, 104 male Wistar rats were randomized in blocks of 5 according to the size of partial hepatectomy to be performed: PH (30) (n = 24), PH (70) (n = 24), PH (90) (n = 24), sham (n = 24) and baseline (n = 8). Each group (not baseline) was further block‐randomized into 3 subgroups according to the day of euthanization: postoperative days (PODs) 1, 3, and 5 (n = 8 per group)(Figure ) in accordance with a previous study conducted by this study group presenting the natural history of liver regeneration in rats subjected to PH (70) PH …”
Section: Methodsmentioning
confidence: 99%
“…In total, 104 male Wistar rats were randomized in blocks of 5 according to the size of partial hepatectomy to be performed: PH (30) (n = 24), PH (70) (n = 24), PH (90) (n = 24), sham (n = 24) and baseline (n = 8). Each group (not baseline) was further block‐randomized into 3 subgroups according to the day of euthanization: postoperative days (PODs) 1, 3, and 5 (n = 8 per group)(Figure ) in accordance with a previous study conducted by this study group presenting the natural history of liver regeneration in rats subjected to PH (70) PH …”
Section: Methodsmentioning
confidence: 99%
“…The binding sites of antibodies were visualized with DAB (Sigma). Negative control slides in the absence of primary antibody were included for each staining [34].…”
Section: Histopathologic Examinationmentioning
confidence: 99%
“…Yet, some animals developed the ability to regenerate, for example amphibian limbs and lizard tails . Mammals have limited ability to regenerate, but studies have shown examples of mammalian regeneration including ear punch hole closure, wound‐induced hair neogenesis (WIHN), liver regeneration after injury and digit tip regeneration . Inbred strains of laboratory mice demonstrate hair follicle regeneration after full‐thickness (FT) wounding, mixed lineage strains show enhanced regeneration and wild African Spiny mice exhibit dorsal skin regeneration even after 60% removal due to FT injury .…”
Section: Introductionmentioning
confidence: 99%